Diagnostic Accuracy of a New d-Dimer Assay (Sclavo Auto d-Dimer) for Exclusion of Deep Vein Thrombosis in Symptomatic Outpatients. (April 2017) - Legnani, Cristina; Cini, Michela; Frascaro, Mirella; Rodorigo, Giuseppina; Sartori, Michelangelo; Cosmi, Benilde
In patients presenting non-high clinical pretest probability (PTP), a negatived -dimer can exclude venous thromboembolism without imaging tests. However, eachd -dimer assay should be validated in prospective studies. We evaluated an automatedd -dimer immunoassay using the Sclavo Autod -dimer (Sclavo Diagnostics Int, Sovicille, Italy) provided by Dasit Diagnostica (Cornaredo, Milan, Italy). Three hundred two consecutive outpatients suspected of leg deep vein thrombosis (DVT) with non-high PTP were included. The Sclavo Autod -dimer assay was evaluated on 2 analyzers (Sysmex CA-7000 and Sysmex CS-2100; Sysmex Corporation, Kobe, Japan, provided by Dasit). The cutoff value (200 ng/mL) was established a priori. Prevalence of DVT was 11.9%. Since no false-negative patients were detected, the sensitivity and negative predictive values (NPVs) were 100% (sensitivity = CA-7000: 100% [95% confidence interval, CI: 93.3-100], CS-2100: 100% [95% CI: 93.3-100]; NPV = CA-7000: 100% [95% CI: 97.9-100], CS-2100: 100% [95% CI: 98.0-100]). Specificity was 65.4% (95% CI: 59.4-71.1) and 69.2% (95% CI: 63.3-74.7) for CA-7000 and CS-2100, respectively. Specificity increased when a higher cutoff value (234 ng/mL) was used for patients aged ≥60 years without compromising the safety. Assay reproducibility was satisfactory at concentrations near the cutoff value (total coefficient of variations <10%). In conclusion, the Sclavo Autod -dimer assay was accurate when used for DVT diagnostic workup in outpatients with non-high PTP. Based on its high sensitivity and NPV, it can be used as a stand-alone test in outpatients with non-high PTP. Given its high specificity, the number of patients in whom further imaging techniques can be avoided increased, improving the yield of the test.